2019
DOI: 10.1101/704379
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell transcriptome profiling reveals dermal and epithelium cell fate decisions during embryonic hair follicle development

Abstract: Characterization of the morphological structure during hair follicle development has been well documented, while the current understanding of the molecular mechanisms involved in follicle development remain limited. Here, using unbiased single-cell RNA sequencing, we analyzed 15,086 single cell transcriptome profiles from E13.5 and E16.5 fetal mice, and newborn mouse (postnatal day 0, P0) dorsal skin cells. Based on t-distributed Stochastic Neighbor Embedding (tSNE) clustering, we identified 14 cell clusters f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 52 publications
(79 reference statements)
1
4
0
Order By: Relevance
“…Similar to the murine model, we also observed differential gene expression profiles in different DP cell populations from different hair follicles (primary hair follicles vs secondary hair follicles), which was also consistent with our recent findings on mice (Ge et al, 2019). Besides, an in-depth comparison of differentially expressed genes revealed that different DP cell populations require different transcriptional profiles, and it’s, therefore, plausible that the different induction signals may be involved during the asynchronous development of hair follicles.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to the murine model, we also observed differential gene expression profiles in different DP cell populations from different hair follicles (primary hair follicles vs secondary hair follicles), which was also consistent with our recent findings on mice (Ge et al, 2019). Besides, an in-depth comparison of differentially expressed genes revealed that different DP cell populations require different transcriptional profiles, and it’s, therefore, plausible that the different induction signals may be involved during the asynchronous development of hair follicles.…”
Section: Discussionsupporting
confidence: 91%
“…Besides, we also compared our identified hair shaft and IRS signature genes with our recently identified murine hair shaft and IRS signature genes (Ge et al, 2019). Interestingly, we only observed about ∼8.8% overlapped IRS signature genes between mouse and goat (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we performed clustering analysis of cells from E13.5 and E14.5 using the Louvain community detection method, respectively. The values of the resolution parameter in the Louvain community detection method were explored to produce the major cell populations in embryonic skin 20,75 . Thus, 11 and 13 cell populations were identified at E13.5 and E14.5, respectively (Supplementary Fig.…”
Section: Joint Learning Of Conserved and Context-specific Communicatimentioning
confidence: 99%
“…2ad). The cell populations were annotated based on the known markers 20,75 . Compared to E13.5, there were two specific populations at E14.5, including dermal condensate (DC) cells and pericytes.…”
Section: Joint Learning Of Conserved and Context-specific Communicatimentioning
confidence: 99%